Pemberdayaan Mustahiq BAZNAS Kabupaten Sukabumi Melalui Program Bangkit Usaha Mikro Berbasis Masjid Desa Peradaban Zakat (BUMI DPZ) - Husnul Khatimah; Nuradi Nuradi (ITB AAS INDONESIA Surakarta, 2021)
BAZNAS Sukabumi Regency has a superior program named Micro Enterprise/ Bangkit Usaha Mikro (BUMI) that based on Zakat Civilization’s Village/ Desa Peradaban Zakat (DPZ) of mosque which is carried out following local socio-cultural community factors, by spiritual and material empowerment at the same time in accordance with its motto ngaji (ruhani) or spiritual empowerment and ngejo (rupiah) or material empowerment. This study aims to determine the success level of the mustahiq empowerment program through the BUMI DPZ program in BAZNAS, Sukabumi Regency. The research that will be used is a survey research by conducting interviews and using a questionnaire, with descriptive analysis methods and qualitative approaches, in the form of collecting facts in the field from interviews in the form of questionnaires to respondents. The results show that the success level of the BUMI DPZ BAZNAS program in Sukabumi Regency in terms of rupiah development is still low due to various obstacles, including the mentality of the assisted residents (mustahiq) who are still in consumptive orientation is still quite difficult to changing to be a productive one and already familiar with the usury system coupled with the limited number of assistants who at the same time have to deal with other institutions that offer assistance programs with interest-bearing loans, even though assistants play a major role in changing the people's mindset as well as agents of change to create empowered community conditions, while in terms of ruhiyah development it can be said to be successful with community assistants activeness to follow routine recitation held by a companion and have routinely issued